2019
DOI: 10.1016/j.jct.2018.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical and structural studies of gallic and ellagic acids

Abstract: We report a study on the energetics and structural properties of gallic (1) and ellagic (2) acids. The experimental values of standard enthalpy of formation in solid state at 298.15 K, 0 m f H  (g) of 2 as (-1128.6  6.4 kJ•mol-1), which was deduced from the isodesmic-reactions methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 34 publications
0
6
0
4
Order By: Relevance
“…Ellagic acid (C 14 H 6 O 8 , EA), an active natural polyphenol ingredient, is extensively found in a variety of fruits and nuts (such as pomegranate, gallnut, blueberry, and grape; Zuccari et al, 2020). The molecular structure of EA contains multiple phenolic hydroxyl groups with strong antioxidant functions (Dávalos et al, 2019). In addition, a large number of studies have confirmed that EA has antibacterial, anti-inflammatory, liver protection, prevention and treatment of obesity, and antitumor effects (Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ellagic acid (C 14 H 6 O 8 , EA), an active natural polyphenol ingredient, is extensively found in a variety of fruits and nuts (such as pomegranate, gallnut, blueberry, and grape; Zuccari et al, 2020). The molecular structure of EA contains multiple phenolic hydroxyl groups with strong antioxidant functions (Dávalos et al, 2019). In addition, a large number of studies have confirmed that EA has antibacterial, anti-inflammatory, liver protection, prevention and treatment of obesity, and antitumor effects (Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular structure of ellagic acid is composed of four fused rings with four hydroxyl groups and two lactone rings representing the hydrophilic part, thus being a dimeric form of gallic acid. The antioxidant property of this compound is related to its molecular structure, particularly the presence and number of hydroxyl groups, the effects of conjugation and resonance, and also the ability to improve the stability of its phenoxy radicals (Dávalos et al, 2019). Ellagic acid directly eliminates reactive oxygen and nitrogen species, such as hydroxyl radicals, hydrogen peroxide, peroxyl, and peroxynitrite radicals.…”
Section: Boletín Latinoamericano Y Del Caribe De Plantas Medicinales Y Aromáticas/ 238mentioning
confidence: 99%
“…5,15 A aplicação direta dos mecanismos de fragmentação na elucidação estrutural tem sido cada dia mais motivada e as revistas especializadas na área de espectrometria de massas conduzem a estudos de mecanismos de dissociação em fase gasosa, que possuam respaldo computacional e embasamento experimental (regido por diferentes análises e técnicas) para que os dados obtidos sejam amplamente utilizados pelos mais diversos usuários. [16][17][18][19][20] Um esquema hipotético dos estudos de Química Computacional usados na interpretação dos espectros de massas pode ser observado na Figura 2. Os estudos computacionais são conduzidos para compreender a reatividade e os mecanismos de fragmentação.…”
Section: Estudos Computacionais E a Espectrometria De Massasunclassified
“…77,85,88 Neste trabalho, os estudos da reatividade em fase gasosa iniciaram-se por alguns derivados da butirolactona mono-e dissubstituídas (Figura 6). Como o objetivo do projeto é o de estudar lactonas que possuam fenilas (moléculas 1-6) e benzilas (moléculas 7-12) como substituintes e derivados da maculalactona (moléculas [20][21][22], mostradas na Figura 6, esse primeiro passo foi realizado, principalmente, em busca da compreensão da reatividade dos núcleos estruturais quando estes compostos possuem tais substituintes.…”
Section: Moléculas Estudadasunclassified
See 1 more Smart Citation